Unveiling English Language Anxiety: Lived Experiences of Nepali Secondary Students in a Multilingual Context - Paneru, Narendra Raj; Bohara, Bhuban Bahadur (Innovative Research Journal, 2025)
The study examines English language anxiety among secondary students in Nepal, a nation marked for its diverse multilingual realities where English has emerged as a marker of socio-cultural prestige and economic privilege. Using the hermeneutic-phenomenological approach, the study investigated the lived experiences of eight purposively selected students from diverse socioeconomic backgrounds through in-depth interviews and thematic analysis; the themes drawn were fear of negative evaluation, low linguistic self-confidence, societal pressures conveying that a person is smart only if he or she is good at English, minimal exposure to English in real life, fear of making mistakes, teacher-student relationship, peer comparisons, and coping mechanisms. Findings reveal that students experience heightened anxiety due to societal expectations that place intelligence and success on being proficient in the English language, coupled, of course, with low exposure to real-world English use. Teacher feedback and classroom environment are equally vital in moderating anxiety; encouraging teachers can help build learner confidence, whereas negative criticism only elevates the fear. Feelings of inadequacy are also increased through peer comparisons; on the other hand, coping strategies like self-affirmation and informal practice reduce anxiety. The study thus highlights the urgent need for training teachers to provide emotional support within pedagogy, training that embraces cultural responsiveness, along with creating further chances for English practice beyond the classroom space. By tackling these socio-psychological impediments, teachers could render the learning environment more inclusive towards learners.